Penggunaan Larutan Fermentasi Kulit Pisang Cavendish dan Garam Terhadap Masa Simpan Filet Nila Merah Berdasarkan Jumlah Mikroba pada Penyimpanan Suhu Rendah - widiastuti, Mia; Liviawaty, Evi; Subiyanto, Subiyanto (Jurnal Kelautan, Lingkungan, dan Perikanan, 2024)
Filet is a food ingredient that is easily damaged and spoiled, so efforts are needed to extend the shelf life of filet by preserving it using low temperature storage and natural preservatives. This research aims to determine the salt concentration in the cavendish banana peel fermentation solution that is best for the shelf life of tilapia fillets. The method used in this research was experimental with four treatments, namely soaking tilapia filets in a fermented solution of cavendish banana peel with a salt concentration of 0%, 2%, 3% and 4% for 30 minutes, then storing at low temperature (5-10̊C). Observations of fillets treated with 0% salt concentration were carried out on days 1, 3, 6, 7, 8 and 9 of storage, while fillets treated with salt concentrations of 2%, 3% and 4% were carried out on days 1, 4, 7, 8, 9, 10, 11, and 12 of storage. The parameters observed were the number of bacteria (TPC) and the degree of acidity (pH), each carried out in duplicate. The research results showed that tilapia filets with 0%, 2%, 3%, and 4% salt cavendish banana skin fermentation solution had storage limits each of up to 6 days 19 hours, 7 days 2 hours, 8 days 8 hours, and 7 days 22 hours. Cavendish banana peel fermentation solution and the addition of 3% salt concentration is the best treatment with a Total Plate Count (TPC) value of 3.6 x 106 cfu/g and a pH value at the storage limit of 6.0, and can inhibit the growth of spoilage bacteria to the limit. maximum storage 8 days 8 hours.